(untitled) (REVISTA DE AGRICULTURA NEOTROPICAL, 2023)
Currently, in modern world science, a large experimental material has been accumulated to search for new forms of nitrogen nutrition of plants and increase the use of nitrogen fertilizers to obtain sustainable crop yields, which is relevant in modern conditions. A science-based fertilizer system should ensure not only the production of planned crops at the lowest cost per unit of production, but also a systematic increase in soil fertility. The purpose of the study was to scientifically substantiate, develop and introduce into the production of agricultural techniques to increase the yield of grain and leguminous crops cultivated on irrigated lands of the North-Western Caspian Sea, which dropped out of active agricultural turnover. The field study was developed on the basis of existing zonal recommendations, complementing them with options for studied agro-receptions. Laying and conducting multifactorial field experiments in various edaphic conditions by the method of split divides was carried out in accordance with the method of B.A. Dospekhov, Fundamentals of Scientific Research in Agronomy. In order to increase the productivity of irrigated land removed from active agricultural turnover, an environmentally sound land use orientation should be envisaged, while maintaining high agricultural productivity.